Нові збірні залізобетонні конструкцій каркасів багатоповерхових будинків і технології їх виготовлення та монтажу - Гнідець, Б. Г.; Гнідець, З. Б.; Hnidets, B. G.; Hnidets, Z. B. (Видавництво Львівської політехніки, 2019)
У багатоповерхових будинках різного призначення протягом багатьох десятиліть застосовували переважно збірні типові каркаси із регулярною сіткою колон і постійною висотою поверхів. Такі типові збірні і нетипові каркаси мають такі недоліки, як різнотипність збірних елементів, висока трудомісткість виготовлення, складність монтажу і вартість будівництва. Для уникнення цих недоліків запропоновано і розроблено нову систему каркасів із нерегулярною сіткою колон і змінною висотою поверхів. У цій системі каркасів прийнято нову, відмінну від типових та інших відомих, схему поділу рам каркасів на збірні елементи, а саме – поділ на великорозмірні однотипні елементи ригелів і колон. Такі однотипні великорозмірні елементи каркаса з’єднуються між собою і стикуються в багатопрогонові не у вузлах, а в зонах нульових моментів у прогонах ригелів. Однотипність збірних елементів ригелів і колон нових каркасів створює умови для виготовлення їх на розробленій авторами одній мобільній технологічній лінії на місці будівництва.

Typical prefabricated carcasses with a regular grid of columns and a constant height of floors were used mostly in the construction of multi-storey buildings for different purposes, for many previous decades. Such typical prefabricated and non-typical carcasses have several drawbacks: diversity of the prefabricated elements, complexity of installation, high work content and cost of construction. During almost half a century, the use of prefabricated reinforced concrete structures has been developed and implemented many typical designs and technologies for their manufacture at factories. For various reasons, prefabricated concrete structures, especially for multi-storey residential frame construction, gradually began to be replaced by monolithic structures. Analysis of the manufacturing cost of prefabricated reinforced concrete structures with the use of outdated technologies at existing factories, the high costs of transportation and installation, shows that the solution of these problems can be realized only with the transition to new structural and technological systems. To do this, it is necessary to develop and implement new multipurpose prefabricated reinforced concrete structures and modern technologies of their manufacture and installation with wide application of complex mechanization, automation, and in the future robotization of all technological processes. A new system of carcasses with irregular grid of columns and variable height of floors is proposed to avoid these drawbacks. In this carcass system a new (distinct of other known and typical examples) scheme of carcass frames dividing on prefabricated elements was accepted, namely: the dividing on large-size identical elements of the beams and columns. These the identical large-size carcass elements are interconnected in nodes and joined into multi-span system not in the knots, but in the points of zero moments in the span of beams or columns. The identity of prefabricated elements of beams and columns for new carcasses creates conditions for manufacturing it on the designed by authors productions line at the construction site.
New prefabricated reinforsted concrete carcasses for multistory buildings and technology of manufacturing and assembling
Keywords: каркас; багатоповерхові системи; будинки; збірні елементи; вузли; з’єднання; перекриття; виготовлення; мобільна технологічна лінія; монтаж; carcass; multi-storey system; buildings; prefabricated elements; production line; nodes; joins; floors; 624.012.4